Mesophotic sponge assemblages in a region undergoing climate change stressors - Donald, Emma P.; Battershill, Christopher N. (Frontiers in Marine Science, 2025)
The biogeography of marine benthic assemblages worldwide is shifting to higher latitudes in response to climate change. Concurrently, extreme weather events are exacerbating environmental stressors. As is typical globally for temperate regions, sponge communities dominate the mesophotic reefs of the Motiti archipelago in the Bay of Plenty (east coast, North Island New Zealand). Although recently classified as a marine reserve for its importance as a refuge for fish and targeted invertebrates (crayfish, abalone/pāua, and sea urchins), the benthos was largely unexplored prior to this research. A series of recent cyclonically associated sedimentation and concurrent marine heatwave events provided an opportunity to examine responses of this benthic-pelagic assemblage important in trophic connectivity. Biogeographic affinities of Motiti’s mesophotic reef benthos were established using remotely operated vehicles (ROVs). Fifty-three sponge species were conservatively identified: 22% representing the southernmost (highest latitude) geographic range recorded to date. Simultaneously, this community may be under threat by the changing marine climate that supported its establishment. Widespread sponge tissue necrosis (especially of Choristid sponges) and sediment smothering of encrusting benthos coincided with the sudden decline of a ‘tumbleweed sponge’ (species unknown). These observations co-occurred with a marine heat wave and major cyclonic event delivering fine sediments to these offshore reefs. This research provides a more nuanced understanding of short- and possibly long-term effects of multiple stressors on mesophotic benthic ecosystems. This newly identified biodiversity hotspot supporting southernmost ranges of Australasian species and its seemingly rapid deterioration, signals a warning for the stability of temperate mesophotic ecosystems.